Les études contrastives et confrontatives: domaine français-polonais - Stefański, Witold (Wydawnictwo Naukowe UAM, 2001)
In this article problems of contrastive and confrontative studies in reference to Polish and French is discussed. The author also deals with the relationship of these studies with typological linguistics. The discussion is based on analyses of oppositions which make it possible to classify languages into analytical and synthetic ones.
Contrastive and confrontative Studies: French-Polish